2000
DOI: 10.1037/0278-7393.26.3.626
|View full text |Cite
|
Sign up to set email alerts
|

Attention and perceptual priming in the perceptual identification task.

Abstract: Prior research indicates that manipulations of attention during encoding sometimes affect perceptual implicit memory. Two hypotheses were investigated. One proposes that manipulations of attention affect perceptual priming only to the extent that they disrupt stimulus identification. The other attributes reduced priming to the disruptive effects of distractor selection. The role of attention was investigated with a variant of the Stroop task in which participants either read words, identified their color, or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
71
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 95 publications
8
71
1
1
Order By: Relevance
“…Second, whenever divided attention fails to impair performance, there is always a risk that the task used to divide attention is not difficult enough (Mulligan, 1997(Mulligan, , 1998Mulligan & Hornstein, 2000). The internal evidence here argues against this.…”
Section: Conceptual Primingmentioning
confidence: 82%
See 4 more Smart Citations
“…Second, whenever divided attention fails to impair performance, there is always a risk that the task used to divide attention is not difficult enough (Mulligan, 1997(Mulligan, , 1998Mulligan & Hornstein, 2000). The internal evidence here argues against this.…”
Section: Conceptual Primingmentioning
confidence: 82%
“…Similarly, Gabrieli et al (1999) reported that keeping track of sequences ofthree consecutive odd numbers reduced priming in exemplar generation, but not in category verification. Nonetheless, Mulligan (1997Mulligan ( , 1998Mulligan & Hornstein, 2000) has shown that varying the difficulty of concurrent activities affects the magnitude ofpriming for some tasks, but not for others. Without systematic manipulation of the attentional requirements of distractor tasks, we cannot conclude with certainty that priming in semantic verification tasks is immune from the effects of divided attention.…”
Section: Conceptual Primingmentioning
confidence: 99%
See 3 more Smart Citations